Bahasa Inggris di Dunia Perhotelan - Berlian Raharjo; Yunita Widiyantari (Sekolah Tinggi Pariwisata Sahid Surakarta, 2013)
Getting hotel as a bussiness nowdays has been a mesmeric bussiness project. No wonder that people eventually put in a race to join this hospitality service icon. One of the most significant things that must be understood by hotel bussiness builders is the ability to cope up all the hospitality desires. Understanding the terms related to it is also a must to guide the line.